Diversity of Family and Social background of students at SANTIPAB High school, LuangPrabang District. Academic year 2018 - 2019 - PHATHOUMVANH, Phanthamanath; KHOTSAIGNOH, Saiphone; THIPPHAPHONE, Kinnaly; SIDAPHONE, Soulinthone; SILIVANH, Sommay; CHANHTHAHONG, Khamxay; INTHAVONG, ViengArnousouk (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The research was conduct in both of quantity and quality method by focus on four of main factor named as Personal factor, family structure factor, family movement factor and community context factor from two group of High score and lower score students; the samples for this research was consist of three groups such as Group 1 the teachers that consist of 9 regular teachers and 6 advisor teachers, Group 2 the 6 persons of student`s parent and Group 3 the 101 students by separating 54 students of high score and 47 of lower. The instrument of this research was consist of questionnaire for the sampling students and interview form for the sampling teacher and parent; researchers testing our questionnaire to ensure that the Item-Objective Congruence Index is acceptable (IOC), finding a percentage (%), finding an averages and Standard Deviation . The research found that: The personal factor was found in low significant and show not different between high score and lower group with Sig. = 0.294. The family structure factor was found in total lower significant different accept the family incomes and daily payment of the student are significant different between two group of student with Sig. = 0.016 and 0.005. The family movement factor of the students was found in significant different statistic particular on parent’s relation and parent’s expectation with Sig. = 0.045 and 0.013. The community factor of the students was found in significant different between 2 group with Sig. = 0.019